The Philippine bases : background for negotiations. Executive summary - Henry, Donald Putnam, 1957-; Crane, Keith, 1953-; Webb, Katharine Watkins; Rand eBooks (Santa Monica, CA : RAND, 1989)
This report assesses the value to the United States and to the Republic of the Philippines of U.S. access to military facilities in the Philippines. Estimates of value for the United States focus on the cost of maintaining existing capabilities through the use of alternative bases and other means. A wide range of alternatives that might provide necessary support for operations stretching from the Persian Gulf to the Pacific Ocean examined and costed. Value for the Philippines is defined more broadly to include U.S. direct input to the Philippine economy through aid payments and base expenditures, as well as estimates of avoided Philippine military expenditures and investor confidence associated with the U.S. presence. The report concludes with suggestions for U.S. policymakers concerning ongoing negotiations with the Republic of the Philippines over the status of the bases.
"August 1989."
"National Defense Research Institute"--Cover.
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Military bases, American -- Philippines; Philippines -- Military relations -- United States; United States -- Military relations -- Philippines; Electronic books